Implementasi Kebijakan Pedoman Analisis Jabatan dan Beban Kerja di Lingkungan Dinas Perhubungan Provinsi Papua Barat - Sabarofek, Markus Lukas; Zaini, Zaman (Reformasi Administrasi, 2024)
The West Papua Department of Transportation has developed a Job Analysis but faces issues with employee competency mismatches. Improvement efforts include the preparation of Standard Operating Procedures and Competency Development Programs. This study employs a qualitative descriptive method to illustrate the Implementation of Job Analysis policies at the West Papua Department of Transportation, involving Interviews and Document analysis with selected informants, focusing on the processes and understanding of phenomena occurring to enhance the agency's performance. The West Papua Department of Transportation requires 101 employees but currently has only 55, indicating a shortfall of 46 employees. This highlights that the Job Analysis and Workload policies have not been effective, as Human Resource Planning, Recruitment, and Workload Distribution are not optimal, necessitating evaluation and strategic improvement steps. Several positions, such as secretary and section head, have not been officially filled despite their duties being carried out by other personnel. This situation is due to a mismatch between Workload and Compensation, as well as a lack of self-development efforts from the existing employees.